2020
DOI: 10.1111/pbi.13488
|View full text |Cite
|
Sign up to set email alerts
|

Bayogenin 3‐O‐cellobioside confers non‐cultivar‐specific defence against the rice blast fungus Pyricularia oryzae

Abstract: Summary Rice cultivars from japonica and indica lineage possess differential resistance against blast fungus as a result of genetic divergence. Whether different rice cultivars also show distinct metabolomic changes in response to P. oryzae, and their role in host resistance, are poorly understood. Here, we examine the responses of six different rice cultivars from japonica and indica lineage challenged with P. oryzae. Both susceptible and resistant rice cultivars expressed several metabolites exclusively duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 66 publications
(73 reference statements)
0
15
0
Order By: Relevance
“…A recent study using iTRAQ found that probenazole-inducible protein 1 (PBZ1) and phenylpropanoid accumulated in both resistant and susceptible cultivars, which was in contrast to reports from previous studies utilizing the 2DE approach (Ma et al 2020b). Interestingly, a metabolomic assay using HPLC identified a rice saponin, Bayogenin 3-O-cellobioside, which is the first saponin found in rice (Norvienyeku et al 2020). Accordingly, the accumulation of Bayogenin 3-Ocellobioside is well corelated with blast resistance.…”
Section: Response Of Rice To Fungimentioning
confidence: 69%
“…A recent study using iTRAQ found that probenazole-inducible protein 1 (PBZ1) and phenylpropanoid accumulated in both resistant and susceptible cultivars, which was in contrast to reports from previous studies utilizing the 2DE approach (Ma et al 2020b). Interestingly, a metabolomic assay using HPLC identified a rice saponin, Bayogenin 3-O-cellobioside, which is the first saponin found in rice (Norvienyeku et al 2020). Accordingly, the accumulation of Bayogenin 3-Ocellobioside is well corelated with blast resistance.…”
Section: Response Of Rice To Fungimentioning
confidence: 69%
“…Also, in the red cotton cultivar, the fungal-pathogen invasion activity of Verticillium dahliae was suppressed because of the enhanced levels of flavonoids (Long et al 2019). Identified Bayogenin 3-O-cellobioside (Norvienyeku et al 2020), probenazole-inducible protein 1 (PBZ1), and phenylpropanoid accumulated (Ma et al 2020) by metabolomics study of rice, are correlated with blast resistance. Metabolomics showed the accumulation of flavonoid compounds and plants coping with C. gloeosporioides by biosynthesis of flavonoid compounds providing potential targets for resistance breeding (Jiang et al 2021).…”
Section: Flavonoidsmentioning
confidence: 99%
“…However, eIF4E role has not yet been reported to have a role in the plant pathogenic fungi, M. oryzae . Here, we identified and deployed cell biology, functional genetic, and biochemical techniques to functionally evaluate the contributions of eukaryotic translation initiation factor eIF4E isoform (MoeIF4E3) to morphological and pathogenic development of the cosmopolitan and economically destructive rice blast fungus pathogen ( Talbot, 2003 ; Norvienyeku et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%